Higher education teachers in Portugal use technology in their educational activities: Myth or Reality? - Peres, Paula (2018)
Technologies are being introduced in our everyday life, including schools and in particular classrooms. Teachers are trying to make the most of web 2.0 tools and social media. However, we are not sure if, in fact, teachers are using these technologies and if when they do, if they do so with pedagogical purposes or to help them to manage the learning process or to replace some obsolete technologies by more modern ones but without learning objectives. To contribute to this question a questionnaire was developed and administered to teachers from higher education. Results show that there is still a long way to go before saying that teachers are fully using and taking the advantages of technologies in the classroom.